Analysis of Dental Teleconsulting in the Pediatric Dentistry Field of Telehealth Minas Gerais: A Cross-Sectional Study - Vanessa Andrade Costa; Lígia Cristelli Paixão; Efigênia Ferreira Ferreira; Antônio Paulino Ribeiro Sobrinho; Renata Castro Martins (Association of Support to Oral Health Research (APESB), 2021)
Objective: To analyze the profile of the dental teleconsulting in the Pediatric Dentistry field of Telehealth Brazil Networks Program, in Minas Gerais centers, Brazil. Material and Methods: Asynchronous dental teleconsulting was evaluated in the Pediatric Dentistry specialty, extracted from secondary databases of the telehealth centers: the Clinical Hospital of the Universidade Federal de Minas Gerais and UFMG Medical School, from July 2015 to July 2017. The variables collected were: type of issues and area and sub-area of Pediatric Dentistry. The results were descriptively analyzed using the SPSS v.22,0 program by frequencies. Results: Most of the issues in the Pediatric Dentistry specialty were about clinical conduct (81.4%). There was a predominance of issues regarding prevention (16.6%), surgery (15.3%), tooth eruption (15.1%), endodontics (12.1%), harmful oral habits (9.7%), patient cooperation (8.7%), primary teeth trauma (7.2%) and dentistry (6.7%). Regarding sub-areas, most issues were related to child oral hygiene (68.5%), tooth extraction (92%), tooth eruption chronology (65.6%), pulp diagnosis (49.0%), bruxism (64%), patient management (74.3%), post-trauma treatment (79.3%), and restoration (88.9%). Conclusion: Pediatric Dentistry teleconsulting suggested a difficulty of the professionals in the pediatric patient approach. Continuing education programs and training courses for professionals working in primary health care are crucial for the comprehensive care of pediatric patients.